Diversity and delay analysis of buffer-aided BICM-OFDM relaying - Islam, Toufiqul; Ikhlef, Aissa; Schober, Robert; Bhargava, Vijay K. (IEEE Transactions on Wireless Communications, 2013)
In this paper, we study a cooperative diversity scheme for wireless systems where the relay is equipped with a buffer. We consider practical frequency-selective channels and adopt the combination of bit interleaved coded modulation and orthogonal frequency division multiplexing (BICM-OFDM). We propose a novel link selection protocol for BICM-OFDM systems where the relay either transmits or receives in a given time slot depending on the quality of the links. We derive a closed-form upper bound for the asymptotic worst-case pairwise error probability (PEP) and the diversity gain of the considered buffer-aided relaying scheme for both infinite and finite buffer size. We show that significant diversity gains can be achieved with buffer-aided relaying compared to conventional relaying at the expense of larger packet delays. In fact, for buffers of infinite (or very large) size, the diversity gain is doubled for links with identical frequency diversity, and an even higher diversity gain advantage is possible for links with non-identical frequency diversities. Furthermore, we perform an exact closed-form average delay analysis for buffers of both finite and infinite size which provides important insight into the achieved delay-performance tradeoff. The derived analytical results and performance gains are corroborated by extensive simulation results. © 2013 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: BICM; Buffer-aided relaying; Cooperative diversity; OFDM